Macroprudential Regulation Under Repo Funding - Valderrama, Laura (IMF Working Papers; Working Paper ;, 2010)
The use of collateral has become one of the most widespread risk mitigation techniques. While it brings stabilizing effects to the individual lender we argue that it may exacerbate systemic risk through margin call activation. We show how a liquidity shock to the cash lender may propagate as a solvency shock via liquidity hoarding even if the cash lender remains solvent in all states of nature. Albeit a cost-effective response of the cash lender to a liquidity shock, liquidity hoarding may lead to the bankruptcy of its repo counterparties triggering contagion across asset classes. To buttress the resilience of the financial system, we lay out a menu of macroprudential policies that deactivate this channel of financial contagion.